PENERAPAN BALANCED SCORECARD SEBAGAI DASAR PENGUKURAN KINERJA PADA KPRI WARTANI GRESIK - Apriliyana, Isma Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out and to analyze the balanced scorecard as the based in measuring the performance. The research methodology is using qualitative method with descriptive analysis technique by using qualitative approach. Based on the result of the performance analysis, it is found current ratio and quick ratio increases but ROI and net profit margin decreases. From the customers perspective point of view the level of customer retention increases, on time delivery shows the increase of the seeds delivery while the number of complain decreases. The internal business perspective of the cooperation has done innovations seeds, in the year of 2011 the cooperation has done the innovation by using the urea fertilizers mix and organic fertilizer, the current payment system is done by the collectors who come to the customers, previously the marketing system is done by giving the counseling. From the growth and the learning perspective which is the employee turnover shows the decrease of the quitting employees, absenteeism shows the decrease in employeeâs absent, the co-operative is doing an appropriate training based on the target.Keywords: Performance Measurement, Balanced Scorecard, Performance Analysis